Osteoblast‐derived NOTUM reduces cortical bone mass in mice and the NOTUM locus is associated with bone mineral density in humans. Issue 10 (15th July 2019) - Movérare-Skrtic, Sofia; Nilsson, Karin H.; Henning, Petra; Funck-Brentano, Thomas; Nethander, Maria; Rivadeneira, Fernando; Nunes, Glaucia Coletto; Koskela, Antti; Tuukkanen, Juha; Tuckermann, Jan; Perret, Christine; Souza, Pedro Paulo Chaves; et al.
ABSTRACT: Osteoporosis is a common skeletal disease, affecting millions of individuals worldwide. Currently used osteoporosis treatments substantially reduce vertebral fracture risk, whereas nonvertebral fracture risk, mainly caused by reduced cortical bone mass, has only moderately been improved by the osteoporosis drugs used, defining an unmet medical need. Because several wingless‐type MMTV integration site family members (WNTs) and modulators of WNT activity are major regulators of bone mass, we hypothesized that NOTUM, a secreted WNT lipase, might modulate bone mass via an inhibition of WNT activity. To characterize the possible role of endogenous NOTUM as a physiologic modulator of bone mass, we developed global, cell‐specific, and inducible Notum ‐inactivated mouse models. Notum expression was high in the cortical bone in mice, and conditional Notum inactivation revealed that osteoblast lineage cells are the principal source of NOTUM in the cortical bone. Osteoblast lineage–specific Notum inactivation increased cortical bone thickness via an increased periosteal circumference. Inducible Notum inactivation in adult mice increased cortical bone thickness as a result of increased periosteal bone formation, and silencing of Notum expression in cultured osteoblasts enhanced osteoblast differentiation. Large‐scale human genetic analyses identified genetic variants mapping to the NOTUM locus that are strongly associated with bone mineral density (BMD) as estimated with quantitative ultrasound in the heel. Thus, osteoblast‐derived NOTUM is an essential local physiologic regulator of cortical bone mass via effects on periosteal bone formation in adult mice, and genetic variants in the NOTUM locus are associated with BMD variation in adult humans. Therapies targeting osteoblast‐derived NOTUM may prevent nonvertebral fractures.—Movérare‐Skrtic, S., Nilsson, K. H., Henning, P., Funck‐Brentano, T., Nethander, M., Rivadeneira, F., Coletto Nunes, G., Koskela, A., Tuukkanen, J., Tuckermann, J., Perret, C., Souza, P. P. C., Lerner, U. H., Ohlsson, C. Osteoblast‐derived NOTUM reduces cortical bone mass in mice and the NOTUM locus is associated with bone mineral density in humans. FASEB J. 33, 11163–11179 (2019). www.fasebj.org